Sectoral distortions and service protection in Russia: A comparison with benchmark emerging markets and EU accession candidates - Rolf J. Langhammer (Kiel Institute for the World Economy (IfW), 2007)
Recent empirical research on efficiency gains for Russia from WTO membership concludes that service trade liberalization especially through allowing foreign suppliers to invest in Russian service industries promises the largest gains. This points to sizable efficiency deficits in the Russian service sector. This paper departs from the question whether both the Russian sectoral protection structure and the effective rates of protection (ERPs) differ from structures and rates in benchmark countries if tax equivalents for intermediate services are taken into account. The result is that almost all Russian service industries get effectively taxed and not protected once not only tax equivalents of intermediate goods but also those of intermediate services are included in ERP calculation. Variance among industries and peak taxes in service industries are significantly higher than in a median emerging country taken as benchmark. These findings support the key role of intermediate services liberalization for the expansion of a viable Russian service sector. Results from comparing Russian effective rates of protection with those of the EU accession countries Bulgaria and Romania are not inclusive. Tax levels of the two accession countries are also high and variant and thus cannot serve as a proxy for the 'economic distance of Russia to Brussels'. Lessons for European Neighborhood Policy point to the requirement for the EU to liberalize bilateral service trade (through mode 3 supply: commercial presence ) on a quid pro quo base: without opening EU markets for Russian companies in specific services (i.e., energy distribution), Russia will probably not open its service sector for EU suppliers more than is required in order to comply with minimum WTO accession prerequisites.
Keywords: F15; F13; 330; Liberalization; Russia; European Neighborhood; Service Trade; Dienstleistungssektor; Protektionismus; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; WTO-Beitritt; Vergleich; Russland; Schwellenländer; Bulgarien; Rumänien